2021
DOI: 10.1371/journal.pone.0248776
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatopathy in pediatric patients after surgery for complex congenital heart disease

Abstract: Patients undergoing complex pediatric cardiac surgery in early infancy are at risk of postoperative secondary end-organ dysfunction. The aim of this study was to determine specific risk factors promoting the development of peri- and postoperative hepatopathy after surgery for congenital heart disease. In this retrospective study, we identified 20 consecutive patients operated between 2011 and 2019 from our institutional cohort who developed significant postsurgical hepatic dysfunction. These patients were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In the pediatric population, NT-proBNP concentrations are notably elevated in individuals with complex congenital heart defects when compared to those with simple cardiac anomalies such as ASD, VSD, or PDA (FERNANDES et al, 2016). Our study's observations of increased NT-proBNP, AST, ALT, Creatinine, and GGT levels align with the literature, which not only highlights these substantial alterations in cases of CHD but also underscores their intricate relationship with hepatopathy (KEHL et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the pediatric population, NT-proBNP concentrations are notably elevated in individuals with complex congenital heart defects when compared to those with simple cardiac anomalies such as ASD, VSD, or PDA (FERNANDES et al, 2016). Our study's observations of increased NT-proBNP, AST, ALT, Creatinine, and GGT levels align with the literature, which not only highlights these substantial alterations in cases of CHD but also underscores their intricate relationship with hepatopathy (KEHL et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, right/left heart dysfunction and the necessity for re-operation or reintervention have been identified as significant risk factors for the development of hepatopathy. These findings emphasize the imperative need for further investigations aimed at reducing hepatic complications and enhancing the prognosis of complex congenital heart disease patients (KEHL et al, 2021;XIE et al, 2021).…”
Section: Discussionmentioning
confidence: 71%
“…Since cardiac surgery poses a traumatic risk for both heart and skeletal muscle, AST levels can rise earlier than alanine aminotransferase (ALT) levels [ 16 ]. Postoperative complications such as pleural effusion, heart rhythm disorders, postoperative infections, and the need for total parenteral nutrition also increase the risk of cardiac hepatopathy [ 17 ]. It was suggested that pediatric patients with elevated transaminases undergoing cardiac surgery are also in the high-risk group in terms of postoperative mortality [ 16 ].…”
Section: Discussionmentioning
confidence: 99%